2008
DOI: 10.1501/tarimbil_0000001047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salinity in Irrigation Water on Some Plant Development Parameters of Sainfoin (Onobrychis viciifolia Scop.) and Soil Salinity

Abstract: Effect of irrigation water salinity was investigated on both the yield and quality of sainfoin and soil salinization under greenhouse conditions in 35 cm wide and 65 cm long PVC columns. Sainfoin was chosen because it is grown in arid and semiarid region with salinity problems and it is cold resistant. 5 levels of water salinity (0.27, 3.5, 7, 10 and 13 dS m -1 ) and two levels of alkalinity (SAR=0.35 and 10) were evaluated as a factorial in a randomized -plot design with three replicates. Sainfoin was harvest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
1
4
0
1
Order By: Relevance
“…According to these results, while the highest plant height was measured in the non-saline soils in 2013, the lowest plant height was determined in the saline soil conditions in 2011. And these results obtained are in agreement with reports of Özaslan Parlak & Parlak (2008). After all, as non-saline soils are more suitable for growth of plants, the plants are able to be a stronger growth and are able to show a better elongation (Li et al 2010).…”
Section: Plant Height (Cm)supporting
confidence: 92%
See 1 more Smart Citation
“…According to these results, while the highest plant height was measured in the non-saline soils in 2013, the lowest plant height was determined in the saline soil conditions in 2011. And these results obtained are in agreement with reports of Özaslan Parlak & Parlak (2008). After all, as non-saline soils are more suitable for growth of plants, the plants are able to be a stronger growth and are able to show a better elongation (Li et al 2010).…”
Section: Plant Height (Cm)supporting
confidence: 92%
“…Salt tolerant plants also have the great potential to ameliorate the saline soils. Of course, yield and quality losses range depending on the type of crop and the severity of the salinity problem (Karakullukçu & Adak 2008;Özaslan Parlak & Parlak 2008). However, there are many forage species that grow under saline conditions, and lot of these have been opportunistically used as fodder for grazing livestock and sustaining livestock production (Grattan et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…En yüksek iki doz olan 75 ve 100 mM uygulamalarında ilerleyen dönemlerde canlı bitki kalmamıştır. Özaslan Parlak (2008), sulama suyu tuzluluğunun korunganın (Onobrychis viciifolia Scop.) verimi ve kalitesi üzerine olan etkilerini ortaya koymak amacıyla yapılan çalışmada, 5 sulama suyu tuzluluğu (0.2, 3.5, , 10 ve 13 dS m -1 ) kullanmışlardır.…”
Section: Bulgular Ve Tartışmaunclassified
“…The members of Onobrychis Miller are important agricultural sources as a forage, fodder legume or ornamental (Ranjbar et al 2010, Carbonero et al 2011. The species of genus also used to improve the quality of the soil by serving fix atmospheric nitrogen and they contribute to the organic structure of soil with root systems (Ozaslan Parlak and Parlak 2008, Arslan and Ertugrul, 2010, Yildiz and Ekiz 2014. Biochemical studies performed Onobrychis Miller taxa showed that the genus have antioxidant, antibacterial and antifungal effects (Karakoca et al 2015, Karamanian and Asadbegy, 2016, Bektas et al 2018).…”
Section: Introductionmentioning
confidence: 99%